PEMAKNAAN TINDAK TUTUR DIREKTIF DALAM KOMIK “YOWAMUSHI PEDAL CHAPTER 87-93” - Arifiany, Nurinna; Ratna, Maharani; Trahutami, Sriwahyu (Japanese Literature, 2016)
This research discusses about speech act of direct in Japanese comic’sYowamushi Pedal Chapter 87-93. Generally, people know that the meaning ofdirectives is give an order or commanding to someone who communication withus. Truthly, directives has another meaning, it depends on the context andsituation. This research purpose to knowing the meaning of directives based onthe context and situation.This research use descriptive method, illocutionary theory of Searle, and“Model of Speaking” of Hymes theory. The result from this research, show thatthere are 4 classifications meaning of directives. There are commanding,requesting, prohibition, and invite expressions.